The Expansion of Lignocellulose Biomass Conversion Into Bioenergy via Nanobiotechnology - Sankaran, Revathy; Markandan, Kalaimani; Khoo, Kuan Shiong; Cheng, Chin Kui; Ashokkumar, Veeramuthu; Deepanraj, B.; Show, Pau Loke (Frontiers in Nanotechnology, 2021)
Lignocellulosic biomass has arisen as a solution to our energy and environmental challenges because it is rich in feedstock that can be converted to biofuels. Converting lignocellulosic biomass to sugar is a complicated system involved in the bioconversion process. There are indeed a variety of techniques that have been utilized in the bioconversion process consisting of physical, chemical, and biological approaches. However, most of them have drawbacks when used on a large scale, which include the high cost of processing, the development of harmful inhibitors, and the detoxification of the inhibitors that have been produced. These constraints, taken together, hinder the effectiveness of current solutions and demand for the invention of a new, productive, cost-effective, and environmentally sustainable technique for LB processing. In this context, the approach of nanotechnology utilizing various nanomaterials and nanoparticles in treating lignocellulose biomass and bioenergy conversion has achieved increased interest and has been explored greatly in recent times. This mini review delves into the application of nanotechnological techniques in the bioconversion of lignocellulose biomass into bioenergy. This review on nanotechnological application in biomass conversion provides insights and development tools for the expansion of new sectors, resulting in excellent value and productivity, contributing to the long-term economic progress.